Perancangan Sistem Pembayaran Sekolah Menggunakan Metode Rapid Application Development (RAD) (Studi Kasus: SMK YAPPIKA Legok) - Paryanto, Agus; Galuh Saputri (LPPM Politeknik Aceh Selatan, 2025)
YAPPIKA Legok Vocational High School is a school that plays a role in the development of science, especially in the fields of Technology and Information. The school payment system still uses manual methods, payments are still made by searching or recording in recapitulation books which takes quite a long time. This research aims to create a school payment system that illustrates the ease of the payment process so that it is more accurate, reliable, representative, and efficient, which can be used to prepare school financial reports. This research can be carried out using the Rapid Application Development (RAD) method to provide faster application development and produce high-quality results than manual methods so that it can be designed and developed quickly, starting from Requirements Planning, Design Processing, and Implementation. The results obtained from this research are developments in time efficiency and performance for Administration in carrying out their work. This can be seen from the time used in processing a payment where the usual time for making a payment is 10-15 minutes which can now be done in a shorter time, namely 3-5 minutes, then payment recapitulation has also decreased in calculation time from 20 -30 minutes to about 5-10 minutes.